Reproductive Rights and Journalism: The Case of Brazilian Women's Spring - Cardoso, Laís Cristine Ferreira; Lima, Nataly de Queiroz; Rocha, Heitor Costa Lima da (Brazilian journalism research, 2018)
This article aims at reflecting on one of the most arid grounds of the discussion regarding gender in journalism: reproductive rights. More specifically, we seek to identify what has been published about the discussion on abortion in the media and the potential of the historical moment, in which new movements reheat the debate on women's rights. To that end, we have collected data, analyzed content, and articulated intersectional theoretical references of the two fields, gender relations and the journalistic field, based on the coverage of the movement of Brazilian women in November 2015, known as Women's Spring, in the national magazines Época and IstoÉ. The analysis of the material has revealed a wide coverage, not criminalizing, but restricted to the traditional discursive rituals that surround topics considered as taboo and which do not fit into a public health framing. Este artigo se propõe a refletir acerca de um dos terrenos mais áridos da discussão de gênero no jornalismo, os direitos reprodutivos. Mais especificamente, buscamos identificar os interditos à discussão sobre o aborto na mídia e as potencialidades do momento histórico, no qual novos movimentos reaquecem o debate sobre os direitos das mulheres. Para tal, articulamos o levantamento de dados, análise de conteúdo e um referencial teórico interseccional aos dois campos, as relações de gênero e o campo jornalístico, utilizando como base a cobertura da movimentação das mulheres brasileiras em novembro de 2015, conhecida como Primavera das Mulheres, nas revistas Época e IstoÉ. A análise do material revelou uma cobertura ampla, não criminalizadora, mas circunscrita aos rituais discursivos tradicionais que se operam em/sobre temas considerados tabus e afastada do enquadramento da saúde pública. Este artículo se propone a reflexionar sobre uno de los terrenos más áridos de la discusión de género en el periodismo, los derechos reproductivos. Más específicamente, buscamos identificar los interdictos a la discusión sobre el aborto en los medios y las potencialidades del momento histórico, en el que nuevos movimientos calientan el debate sobre los derechos de las mujeres. Para tal, articulamos el levantamiento de datos, análisis de contenido y un referencial teórico interseccional a los dos campos, las relaciones de género y el campo periodístico, utilizando como base la cobertura del movimiento de las mujeres brasileñas en noviembre de 2015, conocida como Primavera de las Mujeres, en las revistas nacionales Época y IstoÉ. El análisis del material reveló una cobertura amplia, no criminalizadora, pero circunscrita a los rituales discursivos tradicionales que se operan en / sobre temas considerados tabúes y alejados del encuadramiento de la salud pública.